Principles of information systems : a managerial approach / Ralph M. Stair, George Walter Reynolds - Stair, Ralph M.
The authors have streamlined this edition to cover the most up-to-date topics in information technology. It acts as a framework, teaching traditional computer concepts within the context of addressing business and organisational needs